Impact of PID on industrial rooftop PV-installations - Buerhop, Claudia; Fecher, Frank; Pickel, Tobias; Patel, Tirth; Zetzmann, Cornelia; Camus, Christian; Hauch, Jens; Brabec, Christoph (Proceedings Volume 10370,Reliability of Photovoltaic Cells, Modules, Components, and Systems X, 2017)
Potential induced degradation (PID) causes severe damage and financial losses even in modern PV-installations. In Germany, approximately 19% of PV-installations suffer from PID and resulting power loss. This paper focuses on the impact of PID in real installations and how different evaluated time intervals influence the performance ratio (PR) and the determined degradation rate. The analysis focuses exemplarily on a 300 kWp PV-system in the Atlantic coastal climate. IR-imaging is used for identifying PID without operation interruption. Historic electric performance data are available from a monitoring system for several years on system level, string level as well as punctually measured module string I-V-curves. The data sets are combined for understanding the PID behavior of this PV plant. The number of PID affected cells within a string varies strongly between 1 to 22% with the string position on the building complex. With increasing number of PID-affected cells the performance ratio decreases down to 60% for daily and monthly periods. Local differences in PID evolution rates are identified. An average PR-reduction of -3.65% per year is found for the PV-plant. On the string level the degradation rate varied up to 8.8% per year depending on the string position and the time period. The analysis reveals that PID generation and evolution in roof-top installations on industrial buildings with locally varying operation conditions can be fairly complex. The results yield that local operating conditions, e.g. ambient weather conditions as well as surrounding conditions on an industrial building, seem to have a dominating impact on the PID evolution rate.
Keywords: potential induced degradation (PID); IR-imaging; performance ratio; performance loss